COMPARATIVE ANALYSIS OF EMOTIONAL PERSONALITY TRAITS OF THE STUDENTS OF MARITIME SCIENCE MAJORS CAUSED BY LONG-TERM STAYING AT SEA - Shevchenko, Rosina; Popovych, Ihor; Spytska, Liana; Nosov, Pavlo; Zinchenko, Serhii; Mateichuk, Vadym; Blynova, Olena (Revista Inclusiones, 2020)
The paper examines the issue of emotional personality changes, occurring in the students of maritime and river transport majors caused by long-term staying at sea. The purpose of the research is to conduct comparative analysis of emotional personality states of the students of maritime and river transport majors before and after staying under conditions of long-term onboard training. Methods: observation, conversation with research participants, methods “ММРІ” and “Beck Depression Inventory”. The paper substantiates that changes are caused by a number of physiological, climatic, social and other factors. It establishes correlation between the features of emotional personality state with the fact of long-term staying at sea in the students of the maritime and river transport major. By the scales “pessimism, depression” (D): 80 Т-points in the group of the senior students, who did onboard training courses, 72 Т-points in the group of the junior students, indicating their low mood, lack of self-confidence, caused by a high level of anxiety in the senior students.